2001
DOI: 10.1007/s004210100450
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle training increases cycling endurance without affecting cardiovascular responses to exercise

Abstract: We tested whether the increased cycling endurance observed after respiratory muscle training (RMT) in healthy sedentary humans was associated with a training-induced increase in cardiac stroke volume (SV) during exercise, similar to the known effect of endurance training. Thirteen subjects underwent RMT by normocapnic hyperpnea, nine underwent aerobic endurance training (cycling and/or running) and fifteen served as non-training controls. Training comprised 40 sessions performed within 15 weeks, where each ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 22 publications
12
97
2
1
Order By: Relevance
“…This device has a two-way piston valve connecting to a rebreathing bag. The size of the rebreathing bag was adjusted to 1.5L for the level of intensity in the respiratory trainig, approximating 50 to 60% of the subject's VC as used by Gawril et al 15) , and the breathing frequency was chosen as the low frequency of 12-13 breaths/min to prevent fatigue or dizziness in patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This device has a two-way piston valve connecting to a rebreathing bag. The size of the rebreathing bag was adjusted to 1.5L for the level of intensity in the respiratory trainig, approximating 50 to 60% of the subject's VC as used by Gawril et al 15) , and the breathing frequency was chosen as the low frequency of 12-13 breaths/min to prevent fatigue or dizziness in patients.…”
Section: Methodsmentioning
confidence: 99%
“…Emphasis has been placed on flexibility, mobility, compliance, strength and endurance of the thoracic cage, and the trunk's primary and accessory muscles, to ensure optimal aeration of the lung fields in stroke patients 14) . The feedback respiratory training device, SpiroTiger (Idiag AG, Volketswil, Switzerland), is thought to provide maximum efficacy in the improvement of respiratory function, endurance for exercise capacity, perception of dyspnea, and quality of life [15][16][17] . Since patients with stroke may exhibit respiratory patterns, like those of restrictive lung disease patterns that are similar to those of patients with spinal cord injury, such as tetraplegia [18][19][20][21] , a feedback respiratory training device for stroke patients would be helpful for improve chest expansion and pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have specifically trained the respiratory muscles have reported either an improvement (16,17,28,33,78,84,119,124,131) or no change (25,29,38,57,92,117,140) in whole body exercise tolerance. A concern with all of these studies, however, is that endurance performance was evaluated using fixed work-rate tasks sustained to the limit of tolerance.…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%
“…[15][16][17] This effect on respiratory muscle function was shown to be greater compared with whole-body exercise training (cycling or running). 18 In addition to improving respiratory muscle capacity, respiratory muscle training has also been shown to reduce the perception of adverse respiratory sensations and to increase the exercise performance in healthy subjects [19][20][21] as well as in patients with impaired lung function. 15,17,22,23 Whether respiratory muscle training in obese patients may also improve respiratory muscle capacity, reduce dyspnea and increase exercise tolerance remains unknown.…”
Section: Introductionmentioning
confidence: 99%